Calculation of the radiative lifetime and optical properties for three-dimensional (3D) hybrid perovskites - Mohammad, Khaled Shehata Baiuomy (My University, 2016)
The combination of effective numerical techniques and scientific intuition to find new and novel types of materials is the process used in the discovery of materials for future technologies. Adding to that, being able to calculate the radiative lifetimes of excitons, exciton properties, and the optical properties by using efficient numerical techniques gives an estimation and identification of the best candidate materials for a solar cell. This approach is inexpensive and stable. Present ab initio methods based on Many-body perturbation theory and density functional theory are capable of predicting these properties with a high enough level of accuracy for most cases. The electronic properties calculated using GaAs as a reference system and the 3D hybird perovskite CH3NH3PbI3 are based on density functional theory. The optical properties are investigated by calculating the dielectric function. The theoretical framework of the radiative lifetime of excitons and calculating the exciton properties are based on Wannier model of the exciton and the Bethe-Salpeter equation.
A dissertation submitted for the fulfilment of the requirements of the degree of Master of Science to the Faculty of Science, Witwatersrand University, Johannesburg. June 2016.
Keywords: Excitons theory; Bethe-Salpeter equation; Three-dimensional imaging--Optical properties